Subjective-Objective Matching Evaluation Approach for Enhanced Dental Images - Siti Arpah Ahmad; Noor Elaiza Abd Khalid; Mohd Nasir Taib; Haslina Taib (Institute of Advanced Engineering and Science, 2018)
Cases of misdiagnosis and variability evaluation among the dentists do happen. The complexity of anatomical structures and the low contrast of the original images are factors that contribute to the problems. Image enhancement is often used to enhance medical images. However, currently limited work has been done in enhancing the dental pathological features. Dentists come from different background in terms of experience, place of study, method of practices and emotional quotient. These are some of the factors that may cause differences in subjective evaluation among dentists. Therefore, this research focused on identifying objective measurements based on dentists’ subjective evaluation on abnormalities’ detection in jaw area. Objective measurement is based on contrast improvement index (CII) and subjective evaluation is derived from dentists’ questionnaire answering. This paper contributes to new knowledge in the initial phase of identifying dental disease characteristics by means of correlation between the subjective and objective evaluation.